PROSTATIC DISORDERS IN CANINES DETERMINED BY ULTRASOUND EXAMINATION AND ECO-GUIDED ASPIRATION CYTOLOGY - Peña N., Susan (2013)
The aim of this study was to determine the frequency and type of prostate disorders in canines through the use of ultrasound and cytology techniques. A total of 62 noncastrated dogs that were patients of the Small Animals Clinic of the Veterinary Faculty of San Marcos University, Lima were used. The ultrasound examination was conducted followed by the ultrasound-guided prostatic aspiration technique. The smears were stained and the cell recognition was done. The effect of age, size, breed and clinical signs on the clinical disorder was evaluated. The results showed that 40 animals (64.5%) had a prostate disorder with any of the two tests. The ultrasound technique showed cysts or abscesses (4.8%), hyperplasia (32.3%), hyperplasia and prostatitis (20.9%), prostatitis (4.8%) and neoplasias (1.6%); while through cytology was found glandular hyperplasia (32.3%), hyperplasia associated to inflammation (16.1%), prostatitis (12.9%) and adenocarcinoma (3.2%). Statistical association was found between age and clinical signs with the presence of prostatic disorders (p<0.05). Also, there was statistical concordance between the diagnose resulting from the two tests (p<0.05), however the correlation was lower in cases of prostatic inflammation (k= 0.315).